2002
DOI: 10.1177/088307380201700511
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Disorders: A Potentially Under-recognized Etiology of Infantile Spasms

Abstract: Infantile spasms represent an age-dependent response of the immature brain to a wide variety of insults. An unselected group of children with infantile spasms were reviewed to determine etiology; a metabolic work-up was undertaken if the etiology was unclear from history and examination (cryptogenic). Of the 56 infants, 34 had a recognizable etiology (symptomatic), 1 had normal development (idiopathic), and 21 had cryptogenic infantile spasms. Among the latter, results of plasma lactate and pyruvate or urine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 15 publications
0
31
0
2
Order By: Relevance
“…40,50 They are, however, easily overlooked as an etiology of IS possibly because of the difficulty to correctly gauge the activity of the respiratory chain complexes, especially when no lactate and/or pyruvate increase is identified in blood and/or CSF. 45,51 We show that exome sequencing is a suitable strategy to identify causative genes in familial WS and potentially IS. Exploiting this approach, we identified a novel homozygous c.1825G4T variant in the universally conserved elongation factor GUF1 in three siblings affected with WS.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…40,50 They are, however, easily overlooked as an etiology of IS possibly because of the difficulty to correctly gauge the activity of the respiratory chain complexes, especially when no lactate and/or pyruvate increase is identified in blood and/or CSF. 45,51 We show that exome sequencing is a suitable strategy to identify causative genes in familial WS and potentially IS. Exploiting this approach, we identified a novel homozygous c.1825G4T variant in the universally conserved elongation factor GUF1 in three siblings affected with WS.…”
Section: Discussionmentioning
confidence: 96%
“…They also showed increased CSF lactate levels, a common feature in Leigh syndrome. 47 Among the 13 patients with IS reported in Shah et al, 45 a possibly causing variant was found only in two monozygotic twin sisters who had increased lactate plasma levels. They carried the m.3243A4G change in the tRNA Leu1 gene, which is commonly associated with MELAS (mitochondrial myopathy, encephalopathy, lactate acidosis and stroke-like episodes; OMIM#540000) syndrome.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[ [63][64][65][66][67][68][69] Olası İmmünolojik Mekanizmalı Epileptik Sendromlar mu etiyolojilerinin düşük bir yüzdesini oluşturmaktadırlar. Dolayısıyla genetik kökenli ve semptomatik olguların dışın-da etiyolojisi açıklanamamış büyük bir grup halen etiyolojisinin aydınlatılmasını beklemektedir.…”
Section: Tedavi Ve Prognozunclassified
“…Ragged-red fibers and abnormal electron transport chain activities are frequently absent, particularly in younger children. Although the A3243G mutation is usually thought of as being causal for MELAS, the mutation is more often associated with maternally inherited diabetes, deafness, cognitive impairment, short stature and/or migraine, as well as a wide variety of other disease manifestations (Wallace DC, et al 200;Shah NS, et al 2002;Harrison TJ, et al 1997;and Majamaa K, et al 1998). 2.…”
Section: Mitochondrial Encephalopathy Lactic Acidosis and Stroke-likmentioning
confidence: 99%